Correlation between Vitamin D Deficiency and Osteopenia in Women Residing in Karachi, Pakistan : Vitamin D Deficiency and Osteopenia in Women - Bocha, Yameen; Haroon, Anita; Zafar, Benish; Perveen, Kahkashan; Akhtar, Naheed; Rathore, Padma; Mushtaque, Saher (Pakistan Journal of Health Sciences, 2025)
Osteopenia is one of the primary health concerns among Pakistani women. Objective: To assess the Correlation Between Vitamin D Deficiency and Osteopenia in Women in Karachi, Pakistan. Methods: A cross-sectional survey was conducted among 200 women in Karachi, Pakistan. A self-reported questionnaire was given to all participants so that they could fill in the demographic data. Only participants who were willing to participate in the study were included, and those who failed to provide any data regarding the status of menopause were excluded. SPSS version 23.0 was used to analyze the data. Results: The 200 women in the study had a high reproductive burden (mean pregnancies = 12), with a mean age of 65.2 years and a BMI of 25.6 kg/m². Age-related decreases in bone mineral density were significant (p=0.0002), and osteoporosis was most prevalent in older age groups. The distribution of vitamin D deficiency across age groups was not statistically significant (p=0.22), but it was associated with ageing (p=0.011). Conclusions: It was concluded that although vitamin D deficiency is common among women, age is a better indicator of deteriorating bone mineral density. Age-focused bone health interventions are needed, as osteoporosis and osteopenia were significantly correlated with advancing age.